Hygiene and Sanitation Practices and the Risk of Morbidity among Children 6–23 Months of Age in Kumbungu District, Ghana. (12th December 2019) - Azupogo, Fusta; Abdul-Rahaman, Fadilatu; Gyanteh, Beatrice; Atosona, Ambrose
Abstract : Background . Poor hygiene and sanitation (WASH) practices are characterised by the manifestation of disease and infections, notably diarrhoea and respiratory tract infections (RTIs) among children. This study aimed to assess the influence of WASH practices on the occurrence of diarrhoea and RTIs among children 6–23 months of age. Methods . An analytical cross-sectional study design was conducted in June 2017. Systematic random sampling technique was used to select 300 mothers/caregivers with children aged 6–23 months from 9 communities in the Kumbungu District. We assessed the WASH practices, socio-demographic characteristics of the households and the occurrence of diarrhoea and RTIs among the children with a semi-structured questionnaire. The Hygiene Improvement Framework observational guide was adapted for household sanitation. Backward binary multiple logistic regression was used to determine the WASH practices that significantly predicted morbidity. Results . About 53% and 55.3% of the children reportedly experienced diarrhoea and RTIs, respectively, two weeks before the survey. Caregiver handwashing with soap after defecation [OR = 0.32 (95% C.I: 0.19, 0.52)] and before feeding [OR = 0.50 (95% C.I: 0.30, 0.84)] as well as washing the child's hands with or without soap before feeding [OR = 0.21 (95% C.I: 0.04, 1.01)] were associated with lower odds of diarrhoea morbidity. The main determinants of RTI morbidity included caregiver handwashing with or without soap after defecation [OR = 0.29 (95% C.I: 0.10, 0.81)] and washing of the child's hands with soap before feeding [OR = 0.60 (95% C.I: 0.37, 0.99)] However, we found no association between household sanitation and diarrhoea as well as RTI among the children. Conclusion . About a half each of the children had diarrhoea and RTI 2 weeks before the survey. The results emphasise the need for urgent targeting of handwashing and waste disposal programmes to avert the high burden of diarrhoea and RTIs among children.